“The Hatred in My Heart”: Challenges and Opportunities of Han Christian Identity in Engaging Uyghur Muslims - Copeland, Michael L. (Mission studies, 2022)
As Han Christians continue to engage in Christian mission, understanding their interaction with Uyghur Muslims gives insights into growing barriers and future possibilities. Oral histories and relevant historical sources qualitatively explain the challenges and opportunities involved in Han Christian interaction with Uyghurs Muslims. The article assesses the historical and current backgrounds of both groups. Comparing self-reported identities and interactions reveal not just their distinctives but also opportunities for connection. Finally, this article discusses these specific opportunities, despite escalating tensions, for continued Han Christian engagement in Christian mission with Uyghurs, especially as it relates to sharing translated scripture.